Disseminated Abscessation Complicated with Bone Marrow Abscess Caused by Arcanobacterium pyogenes in a Goat - LIN, Cheng-Chung; CHEN, Ter-Hsin; SHYU, Ching-Lin; SU, Nan-Yu; CHAN, Jacky Peng-Wen (Journal of Veterinary Medical Science, 2010)
An 8-month-old, Nubian wether with a history of systemic illness was euthanatized for a pathological examination. At necropsy, the presence of disseminated abscessation and cellulitis in the limbs was noted. Other postmortem findings associated with the visceral disease in this animal included multiple abscess lesions, mainly in the lungs, kidneys, phalanxes and vertebrae. Histopathologically, lesions of arteriolitis were found as evidenced by bacterial embolisms in pulmonary and renal arteriola, indicating a bacteremia in the patient. Arcanobacterium pyogenes was consistently isolated from 8 lesions of abscessations, including the lesions of subcutaneous abscesses as well as bone marrow abscess in phalanxes and thoracic vertebrae. This is the first published report of disseminated arcanobacterial infection with bone marrow abscess of both the phalanxes and vertebrae in goat.